"Paid to Endure": Paid Research Participation, Passivity, and the Goods of Work - Malmqvist, Erik (American journal of bioethics, 2019)
A growing literature documents the existence of individuals who make a living by participating in phase I clinical trials for money. Several scholars have noted that the concerns about risks, consent, and exploitation raised by this phenomenon apply to many (other) jobs, too, and therefore proposed improving subject protections by regulating phase I trial participation as work. This article contributes to the debate over this proposal by exploring a largely neglected worry. Unlike most (other) workers, subjects are not paid to produce or achieve anything but to have things done to them. I argue that this passivity is problematic for reasons of distributive justice. Specifically, it fails to enable subjects to realize what Gheaus and Herzog call "the goods of work"-a failure not offset by adequate opportunities to realize these goods outside of the research context. I also consider whether granting subjects worker-type protections would accommodate this concern.